Computational analysis and optimization of daylight collector geometry for removal of hotspots in circular mirror light pipe - Singh Bisht, Devendra; Kumar, Vikas; Singh, Simranjit; Garg, Harry; Shravana Kumar, R.R. (Solar energy, 2023)
[Display omitted] •Illuminance patterns analysis on the various surfaces of a tubular daylight guidance system (TDGS).•TDGS comprises a parabolic profiled daylight collector with a prismatic cover sideways and a diffuser as the top.•Proposed design of TDGS results in a significant reduction in light concentration zones.•No compromise in the photometric light transmission.•Light distribution at the exit aperture of long-length mirror light pipe is relatively better.•Enhanced values of illuminance under low altitude beam sunlight and diffuse skylight. The illuminance patterns formed on the various surfaces of a tubular daylight guidance system (TDGS) were numerically measured and calculated for the beam sunlight input. For this study, the TDGS comprises a revolved parabolic profiled daylight collector geometry and a vertical MLP system for daylight guidance. TDGS is basically a non-imaging optical system that is designed to efficiently transmit available sunlight across the MLP (mirror light pipe) length. But while doing so the problematic hotspots are observed mainly on the diffuser placed at the exit aperture of cylindrical MLP which further results in non-uniform illumination in the daylit room. In this work, the use of a prismatic casing arranged sideways to the parabolic profiled collector and a sloped diffuser as a top cover shows a significant reduction in the hotspot problem on the exit aperture of MLP without compromising light transmission in TDGS. The ‘non-uniformity’ index value, Ir signifying the ratio of maximum illuminance to average illuminance on the diffuser surface dropped considerably for the proposed design signifying an increase in uniformity on the exit aperture of MLP. For 1 m long MLP (aspect ratio = 2.5), the maximum value of Ir was ∼ 19 and ∼ 37 for TDGS with dome collector and TDGS with parabolic collector having plane cover (TSA) respectively on midday timings of 21st June while for the proposed design the value was Ir < 5. For 2 m long MLP (aspect ratio = 5), the value was Ir < 4 much lower in comparison to Ir of ∼ 20 and ∼ 36 for TS with dome collector and TSA respectively. A considerable decrease in the severity of hotspots was realized from the results. The proposed collector design was also tested for the illuminance values on the work plane of the simulated room under beam sunlight, diffuse skylight, and overcast sky conditions. No compromise in the average illuminance values was observed when compared to the parabolic collector with transparent casing. Moreover, the proposed design gave enhanced values of illuminance under low altitude beam sunlight as well as under diffuse skylight for various timings of the day. Performance under the overcast sky was found slightly lesser in comparison to conventional collector designs though nominal levels of illuminance were observed for all the configurations of collectors due to the very less magnitude of light availability.